The Effect of Cash Conversion Cycle on Corporate Profitability: A Non-Linear Approach in Indonesian Food and Beverage Companies - Cindy Anggika; Buddi Wibowo (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Working capital management is crucial for maintaining operational efficiency and profitability, particularly in the food and beverage industry, which is characterized by intensive inventory turnover and continuous cash flow requirements. This study aims to examine the effect of the cash conversion cycle on corporate profitability and determine whether the relationship follows an inverted U-shaped non-linear pattern among food and beverage companies. A quantitative approach with a confirmatory research design was employed using balanced panel data from 13 companies over the 2015–2025 period, resulting in 143 firm-year observations. The data were analyzed using panel data regression, with the fixed effects model selected based on model specification tests and robust standard errors. Corporate profitability was measured using EBIT to total assets, while cash conversion cycle and its squared term were the main explanatory variables, with current ratio, sales growth, debt ratio, firm size, and a COVID-19 dummy included as control variables. The findings indicate that cash conversion cycle has a negative and significant effect on profitability at the 10% level, whereas CCC² is statistically insignificant. Firm size has a positive and significant effect, while the COVID-19 dummy has a negative and significant effect. Therefore, the hypothesized inverted U-shaped relationship is not supported.